Drilling of CFRP, GFRP, glare type composites. Issue 4 (1st July 2014) - Tyczyński, Piotr; Lemańczyk, Jan; Ostrowski, Robert; Ewa S´liwa, Romana
Abstract : Purpose: – The purpose of this paper is to analyze machinability of CFRP, GFRP, GLARE-type composites in drilling process taking into account their features and properties (the geometric characteristics, the volume fraction and the mechanical properties of the individual components of the composite). Drilling in non-plan surfaces and slope drilling. Design/methodology/approach: – The tests were carried out in two stages: perpendicular drilling of materials such as GLARE with special drill bits, and drilling of composite structures with non-planar surfaces made of unidirectional carbon fiber prepregs, using the modified special drill. Measurement of cutting forces and torque, stress distribution (photoelastic method) and a visual assessment of defects occurring during drilling allowed to determine the relationship between the type and geometry of the composite drill. Findings: – Identified great effect of kind of composite on the machinability of these materials has substantiated modification of the standard geometry of drills and matching this geometry to specific properties of the various type of composites. Practical implications: – Drilling of assembly holes for aerospace parts. Originality/value: – New type of drill geometry for different type of composite.